The natural history of multiple sclerosis. - Ebers, G (2000)
The natural history of chronic diseases is generally poorly understood. Multiple sclerosis is one of the best-studied diseases and we outline here some of the information obtained from 25,000 patient-years of observation. This population-based cohort received almost no treatment and certainly none known to alter the long-term natural course of the illness. There is a possibility that such data will prove useful in new generation clinical trials which are observational in nature.